Kazuo Ishiguro, Klara e il sole (trad. it. Susanna Basso. Torino, Einaudi, 2021, 269 pp ISBN: 978-88-06-25356-1) (Altre Modernità, 2025)
Kazuo Ishiguro, Klara e il sole (trad. it. Susanna Basso. Torino, Einaudi, 2021, 269 pp ISBN: 978-88-06-25356-1) di Sofia Rossatelli